The Mediating Effects of Brand Image and Brand Love on the Relationship Between Corporate Social Responsibility and Consumer Loyalty. - Veas-Gonzalez, I. (2025)
This study analyzes the complex relationship between Corporate Social Responsibility (CSR) and Brand Loyalty (BLy) among consumers of mobile phone services, particularly examining how Brand Image (BIm) and Brand Love (BLv) act as mediating factors in this relationship. Quantitative research with a correlational scope and cross-sectional design was conducted among 296 consumers of mobile phone services. A questionnaire comprising 26 questions was administered, with responses quantified using a five-point Likert scale. The results were processed using Confirmatory Factor Analysis and partial least squares structural equation modeling (PLS-SEM). This study revealed that CSR alone does not have a direct and significant association with BLy; however, it is associated with BIm and BLv. Furthermore, BIm and BLv were also found to be associated with BLy, demonstrating that the link between CSR and BLy is indirectly built by strengthening BIm and BLv, rather than directly. The originality of this research stems from its concurrent incorporation of BIm and BLv as mediating variables in the link between CSR and BLy.